MANAJEMEN PEMASARAN HOTEL UNTUK DALAM MEMPERTAHANKAN PELANGGAN DI MASA NEW NORMAL - Kadar Nurjaman; Fadil Majid (AKSELERASI: Jurnal Ilmiah Nasional, 2021)
This article reports on hotel business disputes around the world to improve the quality of their service to customers at a time when fierce competition is struggling to keep operating costs as low as possible. Hotel Indonesia operators must prepare themselves to face digital technology to add value to their products and services guided by effective marketing strategies and activities. In addition, they need to face the challenges of the Covid-19 crisis and new standards of hygiene safety standards in the hotel industry in the country. Tourist behavior has changed in the adjustment of safety precautions to prevent Covid-19 infection, and so have their attitudes towards sanitary safety standards. More attention to the cleanliness of the food and facilities in the hotel. This paper reviews the adjustments and potential of the hotel business in dealing with Covid-19; problems or limitations identified in the study; the limitations of handling Covid-19 for the expected success; and transfer of experience and awareness of adjustment to the new normal.